ENT 530 Social Media Portfolio: Giftshop Stylish Headscarf / Amierul Afeeq Rudie - Rudie, Amierul Afeeq (2021)
GiftShop.Stylish is a company based in Kelantan. We sell woman’s apparel specialize in woman’s headscarf or tudung. The company is only for part time as I am currently studying full time at UiTM Puncak Alam. However, during mid semester break me, my brother and a friend decided to make an extra income during our free time. We decided to create our own product, redesign and rebrand those products. Since Kelantan have a lot of Scarf suppliers that are selling it very cheap that were made in Thailand and were selling it at a wholesale, we had the advantage of getting our raw material and premade scarf at such a low price. For one scarf we get around Rm5-Rm10 per pieces and able to buy it in bulk. The redesigning and the rebrand in the product per pieces cost us around RM5-Rm7 depends on how heavy the product needed to be redesign. GiftShop.Stylish start to operate in Kelantan in late September 2020. During that time all 3 of us were on our mid semester break. We started selling it without any brand and new innovation. It started to grab many customers and attention from them. We were able to scale up our business. From there we decided to create our own tags, brand and designs that generate higher profit and our company brand. The scarf is popular among students and workers since it is very cheap and very comfortable scarf to be worn. Hence, the scarf had the advantage of having a merely similar raw material from the big brand such as duck scarf, SugarScarf and etc. However, those big company is not our competitor as we are selling it at such low and affordable price to our customers. That’s when we realized that it could scale up much higher since, we had the best quality and materials that satisfy customers very well. To increase our business profit and sales. We have done some research that nowadays e-platform and e-commerce have becoming a trend. We created a Facebook page and learn to use teaser, soft sell and hard sell to penetrate the target market. Using this platform as an advertising tools we were able to reach many customers and the page insight kept us in track about customer’s behavior and create new strategy for our upcoming product.